EMPLOYEE LOYALTY THROUGH THE ROLE OF JOB SATISFACTION AS A MEDIATOR: LEADER MEMBER EXCHANGE AND WORK LIFE BALANCE AT PT. BATANG HARI BARISAN - Mulyani, Siti Rizki; Yeni, Fitri; Yuliza, Mai (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
This research investigates the role of job satisfaction as a mediator in the impact of leader member exchange and work-life balance on employee loyalty at PT Batang Hari Barisan. Data were collected through surveys and questionnaires distributed to a sample of 74 respondents. Path analysis was used as the analysis method, with SmartPLS used for statistical processing. The findings show that leader member exchange and work-life balance significantly influence job satisfaction. Furthermore, leader member exchange has a significant influence on employee loyalty, while work-life balance has no direct impact on employee loyalty. Job satisfaction was found to significantly influence employee loyalty. In addition, leader member exchange impacts employee loyalty indirectly through the mediation of job satisfaction, whereas job satisfaction does not mediate the relationship between work-life balance and employee loyalty.